(untitled) (E Global Congress, 2023)
This article explores the emergence of pulmonary fibrosis as a consequential and often debilitating outcome of COVID-19 infection. As the global pandemic continues to evolve, a growing body of evidence highlights the association between COVID-19 and the development of pulmonary fibrosis, a progressive and irreversible lung disorder. The article delves into the pathophysiological mechanisms, clinical manifestations, diagnostic approaches, and potential therapeutic strategies for managing COVID-19-induced pulmonary fibrosis. By shedding light on this critical issue, the article contributes to our understanding of the long-term health implications of COVID-19 and the importance of early intervention and research in combating this life-altering consequence.